EFEKTIVITAS GOOGLE CLASSROOM PADA KEMAMPUAN GEOMETRIS MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA KELAS REGULER DAN NON T.A. 19-2 - Marchasan Lexbin Elvi Judah Riajanto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The problem began at the beginning of the emergence of the COVID pandemic 19 in Indonesia, which continued to the necessity of learning as the only possible choice for the implementation of further lecture activities. Researchers view the importance of seeing the effectiveness of the treatment in this case the GC used in the achievement of the objectives of the lecture geometry euclides. The things that researchers pointed out in advance are reasons for researchers to designate research as comparative causal research, along with that involving students' initial ability in the form of a score from quiz 1 that measures the ability of geometric mechanical understanding of schools to the level of C5 thinking ability in bloom taxonomies that researchers have to obtain at the end of the first meeting and the geometric abilities of students obtained based on UTS scores. The analysis of spss17-assisted data was carried out based on the class and the mathematical abilities of the medium and high students of the two classes. From the findings, it was concluded that; Geometric ability of regular class students and non-regular classes after receiving treatment with GC is not different even though the initial ability of the two classes is different based on the quiz 1 score, so learning lectures with the treatment of google classroom can be both used as media and the treatment of geometry courses for regular class and class euclides non-regular in situations and conditions is minimal enough.